2013
DOI: 10.1515/bot-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophytes of the seagrasses Halodule wrightii and Thalassia testudinum in the north-central Gulf of Mexico

Abstract: The purpose of this note is to communicate the diversity of endophytic fungi isolated from living leaves of Halodule wrightii and Thalassia testudinum, two ubiqui tous seagrasses in the northcentral Gulf of Mexico. Fungi were isolated from surfacesterilized leaf fragments of the two plants that had been inoculated onto seawater malt extract agar. Leaves of T. testudinum harbored slightly more endophyte taxa than those of H. wrightii. Trichocladium alopallonellum and 10 other fungal taxa are new records for H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…On the other hand, this lack might be as well due to comparably lower attention paid to seagrasses, especially in comparison with other plant guilds hosting mycorrhizal fungi, including freshwater aquatic plants and plants from saltmarshes and mangroves [15][16][17]. Nevertheless, similarly to terrestrial plants, seagrasses host endophytic fungi [18][19][20][21][22], although their ecophysiological function in the marine environment has not yet been understood. Fungal endophytes are commonly defined as mycobionts which live inside living plant tissues, lack localized interfaces or specialized hyphae for nutrient transfer, do not synchronize their development with plant development, and do not provide nutritional benefits to the plant [23].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this lack might be as well due to comparably lower attention paid to seagrasses, especially in comparison with other plant guilds hosting mycorrhizal fungi, including freshwater aquatic plants and plants from saltmarshes and mangroves [15][16][17]. Nevertheless, similarly to terrestrial plants, seagrasses host endophytic fungi [18][19][20][21][22], although their ecophysiological function in the marine environment has not yet been understood. Fungal endophytes are commonly defined as mycobionts which live inside living plant tissues, lack localized interfaces or specialized hyphae for nutrient transfer, do not synchronize their development with plant development, and do not provide nutritional benefits to the plant [23].…”
Section: Introductionmentioning
confidence: 99%
“…and Cladosporium sp. have been previously reported as the dominant fungi of leaves in other culture-based studies of Z. marina (Shoemaker & Wyllie-Echeverria, 2013;Kirichuk & Pivkin, 2015;Petersen et al, 2019), other seagrass species (Alva et al, 2002;Devarajan & Suryanarayanan, 2002;Rodriguez, 2008;Sakayaroj et al, 2010;Mata & Cebrián, 2013;Venkatachalam et al, 2015) and freshwater aquatic plants (Sandberg et al, 2014). Additionally, Penicillium sp.…”
Section: Discussionmentioning
confidence: 81%
“…Culture-based studies have found fungi associated with leaves, roots and rhizomes of seagrasses, but there is little agreement between studies about the taxonomic composition of these communities within and between seagrass species (Newell, 1981;Kuo, 1984;Cuomo et al, 1985;Devarajan & Suryanarayanan, 2002;Sakayaroj et al, 2010;Mata & Cebrián, 2013;Shoemaker & Wyllie-Echeverria, 2013;Supaphon et al, 2013Supaphon et al, , 2014Supaphon et al, , 2017Panno et al, 2013;Kirichuk & Pivkin, 2015;Venkatachalam, 2015;Venkatachalam et al, 2015;Torta et al, 2015;Ling et al, 2015;Vohník et al, 2016). Recently culture-independent studies of seagrassassociated fungi have more thoroughly investigated the diversity of these microorganisms and highlighted a need to further understand factors affecting their biogeography and community dynamics (Wainwright et al, 2018(Wainwright et al, , 2019Hurtado-McCormick et al, 2019;Ettinger & Eisen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These include Thalassia testudinum, Halodule bermudensis and Syringodium filiforme from Bermuda, USA (Wilson, 1998), T. testudinum, Z. marina and Z. Japonica from Hong Kong and The Philippines (Alva et al, 2002), Halophila ovalis from India (Devarajan et al, 2002), T. testudinum from Puerto Rico (Rodriguez, 2008), Enhalus acoroides from Thailand (Sakayaroj et al, 2010), Halodule wrightii and T. testudinum from Gulf of Mexico (Mata and Cebri an, 2013) and Zostera marina, Z. japonica and Phyllospadix scouleri from San Juan Archipelago, Washington State, USA (Shoemaker and Wyllie-Echeverria, 2013). We now report a Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies reveal that marine macroalgae harbour endophytes exhibiting technologically desirable properties (Zuccaro et al, 2008;Suryanarayanan et al, 2010;Flewelling et al, 2013;Suryanarayanan and Johnson, 2014). Studies on endophyte association of seagrasses include those of Newell and Fell (1980), Wilson (1998), Alva et al (2002), Devarajan et al (2002), Sakayaroj et al (2010), Mata and Cebri an (2013) and Shoemaker and Wyllie-Echeverria (2013). These pertain to studies on one or a few species of seagrasses.…”
Section: Introductionmentioning
confidence: 99%